Predictive factors for surgical outcome in anterior clinoidal meningiomas: Analysis of 59 consecutive surgically treated cases. Issue 15 (April 2017) - Kim, Ju-Hwi; Jang, Woo-Youl; Jung, Tae-Young; Kim, In-Young; Lee, Kyung-Hwa; Kang, Woo Dae; Kim, Seul-Kee; Moon, Kyung-Sub; Jung, Shin
Abstract : Abstract: Despite the advances in the microsurgical technique and anatomical understanding of the anterior and middle skull base, anterior clinoidal meningiomas are still challenging lesions to resect completely and safely due to their intimate relationship with vital neurovascular structures. We report predictive factors for tumor recurrence and postoperative complications based on surgical outcome of patients with anterior clinoidal meningiomas treated at our institution. Fifty-nine consecutive patients with anterior clinoidal meningioma who were surgically treated between March, 1993, and July, 2015, were reviewed retrospectively. For microsurgical tumor removal, orbitocranial or orbitozygomatic (78.0%), extended pterional (15.3%) and subfrontal approach (6.8%) were performed. The median follow-up duration was 54.1 months. Gross total resection (GTR, Simpson's grade I or II) was achieved in 38 patients (64.4%). The overall recurrence rate (new lesion in GTR cases and re-growth in non-GTR cases) was 18.6%. GTR (Hazard ratio [HR] 0.014, 95% confidence interval [CI] 0.001–0.256; P = .004), absence of internal feeder (HR 0.058, 95% CI 0.004–0.759; P = .030) and benign pathology (WHO grade I, HR 0.056, 95% CI 0.005–0.674; P = .023) were independent prognostic factors for recurrence-free. Fourteen patients (23.7%) developed permanent complications. The most common complication was cranial nerve injury (n = 6; 10.2%), followed by postoperative hemorrhage/infarction, hydrocephalus and infection. Larger size (≥ 40 mm) was significant as an independent predictive factor for permanent complication (HR 0.139, 95% CI 0.030–0.653; P = .012). Old age (≥60 years, P = .056) and peritumoral edema (thickness ≥ 5 mm, P = .303) did not reach statistical significance in multivariate analysis. In surgical resection of anterior clinoidal meningiomas, various clinicoradiological factors were related with resection degree, complication, and progression rate. Although our results showed acceptable resection degree and morbidity, mortality, and recurrence rate, compared to the results of past, anterior clinoidal meningioma remain as neurosurgical challenges because of their close contact to critical vascular and neural structures.